Bubble Trouble--Are British House Prices Significantly Overvalued? - Cameron, G; Muellbauer, J; Murphy, A (2006)
The OECD last December said British house prices were overvalued by 30% or more. There has been much talk, including in a 2005 speech by Gordon Brown, of a house price bubble. This article, by Gavin Cameron, John Muellbauer and Anthony Murphy of Oxford University, finds no significant evidence for a bubble from a dynamic panel data model of British regional house prices between 1972 and 2003. The model consists of a system of inverted housing demand equations, incorporating spatial interactions and lags and relevant spatial parameter heterogeneity. The results are data consistent, with plausible long-run solutions and include a full range of explanatory variables. Novel features of the model include transaction cost effects influencing the speed of adjustment and housing market flows, as well as stocks, driving prices. Furthermore, the model allows for shifts in real and nominal interest rate effects as credit markets liberalised.